Chapter 5. The theory of money: an analysis of cryptocurrency in a faith-based finance paradigm - Alamad, Samir (Islamic finance in the digital age, 2024)
This chapter explores how religious rules serve as directives for accounting and auditing practices in Islamic Financial Institutions (IFIs). It examines the concept of money and cryptocurrency within the theory of money and its application in a faith-based context, amid differing opinions among its practitioners. Additionally, the study contributes to studies of money, accounting, and auditing in faith-based organizations by identifying two core concepts: today’s money is not a commodity, in contrast to the capitalist theory of money, and how this distinction influences the faith-based perspective on the emerging phenomenon of cryptocurrencies and assets (CC). The interpretation of money and the view of CC under faith-based rules facilitate coordination among global actors with intersecting religious values, logics, and interests. IFIs strive to integrate their faith-based accounting and auditing of financial transactions with the logics of global financial markets and future financial technologies, ensuring compatibility and relevance.